Cryptic Currencies: Bitcoin at its Peak - Lee, Cheng-Wen; Ivagov, Esentur (Metris: Jurnal Sains dan Teknologi, 2018)
The cryptocurrencies are digital currencies that were initially designated to replace the old ones. However, they act as investment assets and many treat them like stocks. The market for cryptocurrencies counts more than 1600 types and the Bitcoin is the first and foremost of all of them. In one year the price of Bitcoin grew staggering 2000 percent. Other currencies have not seen this type of rising. This study investigates the period of over 4 years of data for 5 cryptocurrencies, the three years before and the last year of hyper-growth of the Bitcoin. We used GARCH model to see if two periods of data may offer some incites for patterns. The findings of this paper show that the Bitcoin in the period of high volatility is more diverged from its counterparts. According to results in the period of high volatility, the factors that influence the price formation of cryptocurrencies may not be the same for all of them. Using the price of the Bitcoin of one day earlier and the price of altcoins today we find spillover effect. Spillover effect is less prominent in the second period of high volatility. It may indicate of relatively independent nature of altcoins during the periods of high volatility.